"Entry to the Society from the Schizophrenic Cave"- A Qualitative Meta-Synthesis of Job Experiences for People with Schizophrenia. (2nd October 2020) - Choi, Dug Ja; Joung, Jeawon; Kim, Eunha; Kim, Sungjae
Abstract: Reviews of employment among people with schizophrenia have primarily encompassed quantitative research. This study analyzes eight qualitative research studies published from 2000 to 2018 on the job experiences of people with schizophrenia to identify participants' job motivations, negative and positive experiences working with schizophrenia, and adaptations to gain social roles and values. We found that the core theme encompassing participants' experiences was the need for social support to facilitate reentry into society from the schizophrenic cave. These results could inform the development of targeted nursing interventions to provide social support and foster job adaptation for people with schizophrenia.